Inhibition of glypican-1 expression induces an activated fibroblast phenotype in a human bone marrow-derived stromal cell-line - Sukhneeraj P. Kaur (Nature Portfolio, 2021)
Abstract Cancer-associated fibroblasts (CAFs) are the most abundant stromal cell type in the tumor microenvironment. CAFs orchestrate tumor-stromal interactions, and contribute to cancer cell growth, metastasis, extracellular matrix (ECM) remodeling, angiogenesis, immunomodulation, and chemoresistance. However, CAFs have not been successfully targeted for the treatment of cancer. The current study elucidates the significance of glypican-1 (GPC-1), a heparan sulfate proteoglycan, in regulating the activation of human bone marrow-derived stromal cells (BSCs) of fibroblast lineage (HS-5). GPC-1 inhibition changed HS-5 cellular and nuclear morphology, and increased cell migration and contractility. GPC-1 inhibition also increased pro-inflammatory signaling and CAF marker expression. GPC-1 induced an activated fibroblast phenotype when HS-5 cells were exposed to prostate cancer cell conditioned media (CCM). Further, treatment of human bone-derived prostate cancer cells (PC-3) with CCM from HS-5 cells exhibiting GPC-1 loss increased prostate cancer cell aggressiveness. Finally, GPC-1 was expressed in mouse tibia bone cells and present during bone loss induced by mouse prostate cancer cells in a murine prostate cancer bone model. These data demonstrate that GPC-1 partially regulates the intrinsic and extrinsic phenotype of human BSCs and transformation into activated fibroblasts, identify novel functions of GPC-1, and suggest that GPC-1 expression in BSCs exerts inhibitory paracrine effects on the prostate cancer cells. This supports the hypothesis that GPC-1 may be a novel pharmacological target for developing anti-CAF therapeutics to control cancer.